The Influence of Leadership Style on Employee Performance in Public Services: A Case Study at The Tempe Village Office, Tempe District, Wajo Regency - Muhammad Isnan Rasyidi; Muh. Syukri; Andi Akbar; Wina Ayu Giswanti; Syamsiar Sulaiman (Pencerah, 2026)
This study aims to analyze in depth the influence of leadership style on employee performance at the Tempe Village Office, Tempe District, Wajo Regency. The main focus of this study is to evaluate how the dynamics of leadership style, including the laissez-faire tendency observed in initial observations, are associated with the effectiveness of village employees' work in the context of public services. The research design uses a quantitative approach with a census method (saturated sampling) on ​​the entire employee population of 11 respondents (4 Civil Servants and 7 non-PNS employees). Data collection was carried out through direct observation, structured interviews, and distribution of Likert-scale questionnaires. The results of the descriptive analysis show that the Leadership Style variable is in the Good category with an accumulative score of 353 from an ideal value of 440. The Employee Performance variable is also categorized as Good with a score of 528 from an ideal value of 715. Pearson correlation analysis shows a very strong positive relationship between leadership style and employee performance of 0.919. Simple linear regression analysis produces the equation Y = 13.804 + 0.919X with a coefficient of determination (R-Square) value of 0.845. This indicates that 84.5% of the variation in employee performance at the study location is associated with perceptions of leadership style, while the remaining 15.5% is influenced by other external factors. Given the limited sample size (11 respondents) as the main limitation, this research is classified as a context-specific micro-bureaucratic case study. Based on these findings, it is recommended that the Tempe Village Head optimize a participatory leadership approach and reduce overly lax (laissez-faire) supervision patterns to encourage sustainable improvements in employee work ethic.